Problems of trade and provision in the daily life of rural regions residents of Central Kazakhstan during 1964-1985 - Saktaganova, Z.G.; Ybyraikhan, M.Y. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
The article discusses the place of trade and supply in the Soviet system, based on a planned economy, and the impact of changes in the daily life of rural regions. The research paper used archival documents and interview materials that were first introduced into scientific circulation. Since the Soviet trade and supply system, which did not take into account demand, could not fully provide the common population with types of goods, the qualities of the “Soviet man” in everyday life always helped to find a way out of the difficult, and the solution of the problem was carried out in the system of institutional and beyond structures. The article takes into account the disadvantages and advantages of providing local differences between districts and types of goods, reflects changes in taste and innovations in human needs. Nomenclature with low interest and zeal for the cause in Soviet institutions, as in other fields of activity of the Soviet era, the most important thing is an ordinary “Soviet man” with the desire to satisfy his basic needs in a rigid state and ideological system are given by examples of rural areas. The primary sources of the habits formation, which in most life situations first give importance to informal contacts, are indicated by clear evidence. In conclusion, it was concluded that the supply of the rural population with consumer goods was completely subordinated to the state, the place of shortages was covered by informal contacts and relations on the local ground, and the common people fought the deficit through the methods of “silent resistance”.
1964-1985 жж. Орталық Қазақстанның ауылдық аймақтары тұрғындарының күнделікті өміріндегі сауда және қамтамасыз ету саласының мәселелері
Проблемы сферы торговли и обеспечения в повседневной жизни жителей сельских регионов Центрального Казахстана в 1964-1985 гг.
Keywords: life; trade; supply; commodity; demand; rural region; Central Kazakhstan; scarce commodity